PCB Test to Assess Critical Thinking in Students from Disadvantaged Contexts (2023)
The study focused on the design of a test to evaluate the critical thinking of university students in the Colombian Caribbean Region, based on the results of the Saber 11 standardized tests, applied by the Colombian Ministry of National Education, to measure the basic competencies of eleventh-grade students, among which is critical reading. The research was developed in three phases: review and theoretical referencing of the different instruments for measuring critical thinking, design of the dimensions and indicators, according to the disadvantaged contexts, and validation of the instrument. The research approach is mixed. The statistical instruments CVI, KMO, exploratory factor analysis, confirmatory factor analysis, and Barlett's test of sphericity reveal reliability in the qualitative categories of the test, confirmatory results in the dimensions and indicators, and coherence among the items. When the pilot test was applied, the conceptual and contextual relationship of the dimensions and indicators was found. The study suggests that the PC-B test is an effective tool for gauging the critical thinking abilities of students from disadvantaged backgrounds